THE The Effect of Corporate Image, Service Quality, Experiential Marketing on Customer Loyalty with Customer Satisfaction as Intervening Variable at PT Yudhistira Perkasa Abadi Surabaya - Ikhwanus Sofa; Sri Handini (Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the effect of Corporate Image, Service Quality, Experiential Marketing on Customer Loyalty, with Customer Satisfaction as a Variable Intervening at PT Yudhistira Perkasa Abadi Surabaya. The population in the study was 57 respondents who met the requirements according to this study. This study uses quantitative methods with random sampling techniques and quantitative/statistical data analysis to test hypotheses. The research location taken was PT Yudhistira Perkasa Abadi Surabaya. Researchers examined this here because this company experienced relatively high tender conditions fluctuations. There was competition for tenders from vendors, which was quite tight. In this study, involving many variables or constructs with a small sample size, this study used Partial Least Square (PLS) analysis. The data processing results show that Corporate Image, Service Quality, and Expential Marketing significantly positively influence Customer Satisfaction. However, Corporate Image does not have a significant influence on Customer Loyalty. Meanwhile, Service Quality, Expential Marketing, and Customer Satisfaction significantly influence Customer Loyalty when mediated by Customer Satisfaction. Future research should consider other variables that affect Customer Loyalty and Customer Satisfaction. Companies can increase customer satisfaction by optimizing marketing and public relations strategies. Public relations can help reduce the gap between customer expectations and the reality they experience. In this case, facilitating the customer user interface by creating applications that facilitate customer access in monitoring the services performed can help build customer satisfaction and strengthen customer communities loyal to the company.